Communication and Contention: The Role of Literacy in Conflicts with ‘Abbāsid Officials - Berkel, Maaike van (History compass, 2007)
‘Abbāsid officials of the late ninth and early tenth centuries operated in a highly bureaucratized and literate environment and they expressed their identity in terms of expertise in writing. However, in their daily business they had to communicate with all kinds of social groups, some of which had not - or only to a certain level - been introduced to writing. During the last three decades a series of groundbreaking studies appeared on the introduction and dissemination of writing in Medieval Europe. The role of literacy in Arab and Islamic societies in this period have as yet received very little, and mainly rather specialized, attention. The communication between ‘Abbāsid officials and other social groups will be studied in cases of conflict and their settlements. Conflict settlement is also a field of research that recently witnessed important new insights. Studying the use of written documents in dispute settlements - a situation in which communication is of vital importance to all parties involved - forms therefore an excellent opportunity to analyse familiarity with, and confidence in, writing among the various groups within the ‘Abbāsid caliphate.